Infectious Bovine Rhinotracheitis Control Program in Slovakia - Mandelik, Rene; Bires, Jozef; Ozsvari, Laszlo; Hodnik, Jaka Jakob; Vilcek, Stefan (Frontiers in Veterinary Science, 2021)
As for other European countries, IBR is a significant cause of financial losses in cattle in Slovakia. The State Veterinary and Food Administration of the Slovak Republic prepared a voluntary IBR control program for cattle farms in 1995, which was implemented in 1996. In subsequent years, 48-119 farms/year enrolled in the voluntary IBR control program. Since the end of 2006, the IBR control program became compulsory by law for all cattle farms in Slovakia. Serology was used to identify infected animals using a conventional ELISA amongst non-vaccinated cattle and a gE specific ELISA in cattle vaccinated with marker vaccine. Eradication is based on culling when the serological prevalence of IBR in a herd is below 15%. When the prevalence is higher than 15%, the culling is combined with the application of a marker vaccine. A radical method where all animals are slaughtered is used with the agreement of the farmer when appropriate, especially for very small herds. Depending upon the selected eradication method, the antibody positive cattle can be gradually replaced in the herds to eliminate financial losses due to the disease. The movement of cattle is under strict control requiring a health certificate issued by the state veterinary authority and the movement must be recorded in the central livestock registry. The next step for herds is monitoring to achieve official IBR-free status. Based on the official figures from The State Veterinary and Food Administration, 60.2% herds were free of IBR in Slovakia in 2020.